2002
DOI: 10.1021/ja011675k
|View full text |Cite
|
Sign up to set email alerts
|

Production, Analysis, and Application of Spatially Resolved Shells in Solid-Phase Polymer Spheres

Abstract: Two-photon fluorescence microscopy has been used to interrogate the interior functionality of polymer resin beads. By employing this technique, the spatial distribution of the initial functionality contained within the polymer matrix has been determined. Spatially resolved, concentric shells were then produced synthetically in these polymer spheres via a series of protection/deprotection reactions in which two-photon fluorescence microscopy was employed to monitor each successive step. To demonstrate the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Since the library compound on the bead surface does not have a cleavable linker, it will never be released and will not affect the MS analysis. 17 The method is based on the fact that the reaction rate of amino protection is significantly faster than the diffusion rate of the protecting agent inside the bead. However, as indicated by the authors in the article, as the synthesis of each layer progresses, the production of each successive layer becomes more difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Since the library compound on the bead surface does not have a cleavable linker, it will never be released and will not affect the MS analysis. 17 The method is based on the fact that the reaction rate of amino protection is significantly faster than the diffusion rate of the protecting agent inside the bead. However, as indicated by the authors in the article, as the synthesis of each layer progresses, the production of each successive layer becomes more difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Farrer et al have reported the generation of multi-layer beads using a chemical method similar to our PAP approach by employing Fmoc-chloride [45]. Concentric bead layers were produced by means of sequential protection and deprotection of the primary amines within the beads.…”
Section: Methods For Generating Topologically Segregated Bilayer Beadsmentioning
confidence: 99%
“…The homogeneity of the loading of the particles was determined by coupling dansyl chloride to the free amine groups followed by analysis using a two-photon microscope [13]. The results of this work are shown in figures 4 and 5.…”
Section: Stirrermentioning
confidence: 98%